Internalisasi Kitab Kuning Nadham Alala dan Aqidatul Awwam di MI al-Maarif 02 Singosari - Rosyidah, Amiliya Nur; Ulum, Achmad Miftachul; Azzahra, Fatimah (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
This study aims to explore and analyze the process of internalizing the classics, especially Nadham Alala and Aqidatul Awwam, in the learning process at MI Al-Maarif 02 Singosari. This research is motivated by the challenges faced by the younger generation today, including moral degradation and religious identity crisis caused by the influence of globalization and modernization. The method used in this research is a qualitative approach with phenomenological techniques, which allows researchers to dive deeply into students' experiences through interviews, observations, and document analysis. The results showed that the classic book internalization program not only succeeded in introducing religious values to students, but also contributed significantly in shaping their noble character and morals. In addition, the study revealed that learning the Islamic classic book provides students with a better understanding of Islamic teachings, as well as increasing their enthusiasm for learning and ability to memorize. From the results of the study, it can be concluded that the internalization of the Islamic classic book is a strategic step in creating a young generation that not only excels in the academic field, but also has spiritual depth and personality in accordance with the guidance of Islamic teachings. This research is expected to contribute to the development of religious education in madrasah and become a reference for other Islamic educational institutions in implementing a curriculum based on the Islamic classic books.